The perception on human thermal comfort and microclimatic condition in a park with different landscape designs - Marikah @ Yusof, Siti Nadiah (2018)
The microclimate and human thermal comfort benefits of urban park are important as the environmental conditions will be affected according to surrounding landscape and will consequently affect those who use the park for recreational activities. Therefore, this study aimed to evaluate the influence of different landscape concepts on microclimatic conditions and human thermal comfort perception. The study site was located at Taman Saujana Hijau at Precinct 11, Putrajaya that has three different landscape concepts namely European Garden, English Garden and Oriental Garden. Microclimate parameters including air temperature, relative humidity, solar radiation and wind speed were measured with 20 sampling points which were established at each garden. ANOVA analysis showed that there were significant differences between microclimate parameters in different landscape concepts suggesting that adding trees and more species to provide better thermal comfort of park users. For human thermal comfort perception measurement, 107 questionnaires were distributed and analyzed by linear regression analysis. The result from regression analysis showed that the park achieved the neutral human thermal comfort thus suggesting that the visitors were thermally satisfied with the environment condition of the English Garden. In addition, the microclimate parameters were clearly greater during noon compared to evening due to heat released. The results from this study will be beneficial for the urban park managers and stakeholders with respect to landscape designs for example, by adding more trees to improve microclimate.